Teori Amandemen dan Proses Amandemen di Indonesia - Muntoha - (Universitas Islam Indonesia, 2003)
The importance of a constitution, as its original character in the western countries, is to determine the limits of power authority, guarantee people rights and regulate the government system. For that reason, the basic requirements for the process of constitution amendment is must be taken away from any short term political interests, if this the case, the results of the amendment certainly will be a non disputable national consensus. Itwill be a ‘final' amendment which passes some transparent procedures and enough sociaiization, and of course, will be far from fait accompli.